Understanding and addressing changing administrative workload in primary care in Canada: protocol for a mixed-method study - Agnes Grudniewicz; M Ruth Lavergne; Emily Gard Marshall; Lindsay Hedden; Madeleine McKay; Ruth Martin-Misener; Myles Leslie; Richard Buote; Catherine Moravac; Fiona Bergin; Julie Easley; Melanie Mooney; et al. (BMJ Open)
Introduction Many Canadians struggle to access the primary care they need while at the same time primary care providers report record levels of stress and overwork. There is an urgent need to understand factors contributing to the gap between a growing per-capita supply of primary care providers and declines in the availability of primary care services. The assumption of responsibility by primary care teams for services previously delivered on an in-patient basis, along with a rise in administrative responsibilities may be factors influencing reduced access to care.Methods and analysis In this mixed-methods study, our first objective is to determine how the volume of services requiring primary care coordination has changed over time in the Canadian provinces of Nova Scotia and New Brunswick. We will collect quantitative administrative data to investigate how services have shifted in ways that may impact administrative workload in primary care. Our second objective is to use qualitative interviews with family physicians, nurse practitioners and administrative team members providing primary care to understand how administrative workload has changed over time. We will then identify priority issues and practical response strategies using two deliberative dialogue events convened with primary care providers, clinical and system leaders, and policy-makers.We will analyse changes in service use data between 2001/2002 and 2021/2022 using annual total counts, rates per capita, rates per primary care provider and per primary care service. We will conduct reflexive thematic analysis to develop themes and to compare and contrast participant responses reflecting differences across disciplines, payment and practice models, and practice settings. Areas of concern and potential solutions raised during interviews will inform deliberative dialogue events.Ethics and dissemination We received research ethics approval from Nova Scotia Health (#1028815). Knowledge translation will occur through dialogue events, academic papers and presentations at national and international conferences.